The Analysis of The Relationship Between Monetary Financing and the General Budget in the United States from 2008 - 2022 - Dadoosh, Ali Abdulkadhim; Buraihi , Dr.Faris Kareem (Journal of Economics and Administrative Sciences, 2024)
Monetary finance is a new policy from economic and political discussions concerning government spending. Until 2008, taxes (oil in oil-producing countries) and debt issuance were considered reasonable methods for understanding the balance of the general budget or financing deficits. Governments financed themselves through present taxation, traditional borrowing with repayment from future tax revenue, or financial surpluses resulting from oil price increases in global markets. However, after 2008, central banks resorted to unprecedented monetary finance policies, issuing large amounts of money to stimulate crisis-affected economies. The study aimed to understand monetary finance as a policy imposed by governments on central banks to finance public expenditure during crises. The paper focused on the issue that the US government's reliance on monetary finance led to inflation and an increased national debt during the study period. The study concluded that the US government resorts to borrowing funds through the sale of treasury bills, bonds, and other securities to the Federal Reserve Bank, resulting in the accumulation of public debt and associated interest payable to investors who bought these securities. Paper type: Paper.